Epigallocatechin-3-Gallate Alleviates High-Fat Diet-Induced Nonalcoholic Fatty Liver Disease via Inhibition of Apoptosis and Promotion of Autophagy through the ROS/MAPK Signaling Pathway. (17th April 2021) - Wu, Dongdong; Liu, Zhengguo; Wang, Yizhen; Zhang, Qianqian; Li, Jianmei; Zhong, Peiyu; Xie, Zhongwen; Ji, Ailing; Li, Yanzhang
Abstract : Nonalcoholic fatty liver disease (NAFLD) represents one of the most common chronic liver diseases in the world. It has been reported that epigallocatechin-3-gallate (EGCG) plays important biological and pharmacological roles in mammalian cells. Nevertheless, the mechanism underlying the beneficial effect of EGCG on the progression of NAFLD has not been fully elucidated. In the present study, the mechanisms of action of EGCG on the growth, apoptosis, and autophagy were examined using oleic acid- (OA-) treated liver cells and the high-fat diet- (HFD-) induced NAFLD mouse model. Administration of EGCG promoted the growth of OA-treated liver cells. EGCG could reduce mitochondrial-dependent apoptosis and increase autophagy possibly via the reactive oxygen species- (ROS-) mediated mitogen-activated protein kinase (MAPK) pathway in OA-treated liver cells. In line with in vitro findings, our in vivo study verified that treatment with EGCG attenuated HFD-induced NAFLD through reduction of apoptosis and promotion of autophagy. EGCG can alleviate HFD-induced NAFLD possibly by decreasing apoptosis and increasing autophagy via the ROS/MAPK pathway. EGCG may be a promising agent for the treatment of NAFLD.